Students 'Understanding and Appreciation of Ethnic Relations Course - Sharil, Suhaila; Ahmad Ubaidah, Ahmad Faiz; Hussin, Muhammad Noor; Abdul Basir, Mukhamad Khafiz (Idealogy Journal; Vol 5 No 2 (2020): Idealogy Journal (September 2020)DO - 10.24191/idealogy.v5i2.236, 2020)
The Ethnic Relations Course is a compulsory university course offered to Bachelor's Degree students at Universiti Teknologi Mara Negeri Sembilan Branch, Rembau Campus. There are two faculties that take this course at UiTM Negeri Sembilan Branch Rembau Campus are students from the Faculty of Information Management and the Faculty of Communication and Media Studies. In session II 2018/2019 a total of 52 students took this course where 37 people were from the Faculty of Information Management and 25 people from the Faculty of Communication and Media Studies. This study was conducted to examine the understanding and identify students' appreciation of the Ethnic Relations course. The methodology of this study uses quantitative research through purposive sampling design. Questionnaires were distributed to all students who took the Ethnic Relations Course in session II 2018/2019, which is a total of 52 respondents. The results of the study found that students' appreciation of this course is very good but the field study that involves focus group discussion makes students very interested in the course of Ethnic Relations even though this course revolves around history.